In situ quantification of fungicide residue on wheat leaf surfaces using matrix-assisted laser desorption/ionization time-of-flight mass spectrometry imaging technology - Xuerui Yang; Mengyao Shi; Minghui Hong; Zhixin Hui; Jiaqi Pan; Guangli Xiu; Lei Zhou (Food Chemistry: X)
To overcome the time-consuming off-site limitations in conventional pesticide detection, this contribution presents an in situ quantitative analysis detection strategy for pesticides on leaf surfaces using matrix-assisted laser desorption/ionization time-of-flight mass spectrometry imaging technology. Taking fungicide metrafenone as a representative, we initially screened seven commonly used matrices, and identifying α-cyano-4-hydroxycinnamic acid as the most effective one in positive mode. Subsequently, coating the matrix using sublimation spraying method resulted in the highest mass intensity. The optimal combination of operation parameters were established with imaging step size of 30 μm × 30 μm, laser diameter of 75 μm, and laser energy of 4.01 μJ/pulse. Under these conditions, a lowest detection limit of 0.6 ng/mm2 was reached for metrafenone, demonstrating extremely high sensitivity and strong repeatability. This method exhibits great potential for the analysis of various pesticides, including triadimefon and tebuconazole, thereby offering innovative approaches to the analysis of pesticide residues.